Incidence of Faecal Coliform in Well Water Obtained from Sabon-Gari Area, Osogbo (Fountain Journal of Natural and Applied Sciences, 2012)
Well water samples obtained from Sabon gari area of Osogbo, Osun state were analysed for the bacteriological qualities, physico-chemical and organoleptic properties. The spread plate technique was adopted using MacConkey, mannitol salt and thiosulphate citrate bile salt sucrose (TCBS) agars. The total coliform, faecal coliform, and staphylococcus counts on MacConkey and mannitol salt agar were 7.3 x 106, 3.9 x 106 and 1.1 x 106 cfu /mL respectively but there was no growth on TCBS agar. Escherichia coli (27%), Klebsiella pnuemoniae (19%), Shigella dysenteriae (25%), Salmonella typhi (16%) and Staphylococcus species (13%) were identified as the major bacteria isolated from the well water. The pH value ranged from 6.25 to 7.93 while the temperature ranged between 26.1 and 28.90C respectively. Microbiological quality is the most important aspect of drinking water in relation to waterborne diseases. Thus, detection of bacterial indicators in drinking water means the presence of pathogenic organisms related waterborne diseases.Keywords: Well water; coliform; incidence rate; pH; temperature; Escherichia coli